The briefcase as an evaluation strategy for post, inter and transdisciplinary studies - Fracapani, Marta; Fazio, Marisa (Acta Bioethica, 2008)
The Bioethics Magister offered by de National University of Cuyo gets together social and human sciences professional and those of the hard sciences, and, among others, insists especially on creating attitudes, such as tolerance, willingness for dialogue and critical judgement. The studies' goal that this woek describes consists in evaluating if the portafolio may be considered as an authentic tool to evaluate the apprenticeship of a postgraduate study, where as its most expected profile consists mainly on forming attitudes. Once two cohorts have been analysed, the partial results demostrate that it is possible to evaluate attitudes, but that it presents difficulties when needing to involve students in that type of evaluation and in establishing an appraisal as objetive as possible. At the time being only one cohort is still missing to put an end to the investigation.